2018
DOI: 10.4236/ojmm.2018.83005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action and Scaring of 10% Green Banana Shell in Chronic Wounds

Abstract: The percentage of diabetic patients with contaminated lesions increases from 3% to 10%. Treatment with herbal products shows benefits in their use, as well as antioxidant and antifungal activities. Objective: to evaluate the antimicrobial action of 10% banana peel gel and the contraction of diabetic and venous wounds. Methods: individual, analytical, interventional, longitudinal, prospective, randomized study from February to December 2015. Five patients were included in the study; 3 with venous ulcer and 2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…14 The use of the gel based on banana extract in chronic leg wounds demonstrated a reduction of antimicrobial activity of up to 99% in 80% of the cases, which shows its efficacy in the management of these lesions. 20 The declaration of rights of the person with an ostomy states that the ostomy patient must have unrestricted access to the variety of accessible ostomy products. 21 It is essential that any equipment or product prescribed for such complications offers resolvability and reliability to the patient, given the emotional changes caused by the condition of being ostomized, as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…14 The use of the gel based on banana extract in chronic leg wounds demonstrated a reduction of antimicrobial activity of up to 99% in 80% of the cases, which shows its efficacy in the management of these lesions. 20 The declaration of rights of the person with an ostomy states that the ostomy patient must have unrestricted access to the variety of accessible ostomy products. 21 It is essential that any equipment or product prescribed for such complications offers resolvability and reliability to the patient, given the emotional changes caused by the condition of being ostomized, as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest recorded as antimicrobial activity is extract from Musa paradisiaca peels [13,14]. This study focused on several concentrations of Musa paradisiaca's peel extract that work effectively against microbes to be formulated into spray gel preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of banana peels into high-value pharmaceutical preparations will provide advantages in the development of health products. Previous studies have demonstrated that the extracts of M. paradisiaca peel could inhibit microbial growth and enhance wound healing in animal models (7). Banana peels have bioactive compounds, according to recent research, which can be used to create products with health benefits like antimicrobial (8)(9)(10) and antioxidant (11)(12)(13) properties.…”
Section: Introductionmentioning
confidence: 99%